The oral manifestations of scurvy in the 21st century (Research, Society and Development, 2021)
Scurvy is a vitamin deficiency historically associated with pirates and sailors that affects collagen synthesis, leading to hemorrhage, skin, and oral lesions. In the 18th century, the lack of consumption of foods rich in vitamin C was found to cause such a severe condition, whose early diagnosis increases the likelihood of a better prognosis. A 58-year-old female patient complained of fatigue, body pain, and gingival bleeding for nearly  24 months. In 2001, she was diagnosed with lupus, now in remission, and osteoporosis more recently. On clinical examination, gingivitis with spontaneous bleeding was observed, despite the patient’s good hygiene, as well as some petechiae over the body. Due to the hypothesis of a possible autoimmune dermatological disease, the patient was referred to a dermatologist, who requested a series of tests, including vitamin C dosage. The results showed a concentration below 0.25mg / dL (IR, 4 to 2.0 mg / dL), and thus the diagnosis of scurvy was established. The patient was administered vitamin C replacement and in about 3 months, the symptoms started to improve. In some cases, such as this, hospitalization is required for intravenous replacement due to bleeding risks. This case report highlights the importance of the dentist in the early diagnosis and treatment of scurvy. This condition causes oral lesions that are often confused with other more common conditions, such as gingivitis or autoimmune dermatological response. Therefore, we recommend a comprehensive physical examination and anamnesis, including dietary history.